Approaches to the total synthesis of synoxazolidinone C - Villa, Maxime (2018)
Chapter 1 starts by showing why anti-fouling natural products became an area of wide interest over the past few decades, giving some background about the main anti-fouling technologies. It is followed by the presentation of various anti-fouling natural products and the key features those compounds have in common with the target molecule of this project, synoxazolidinone C. The oxazolidinone and 4-oxazolidinone cores are shown in a few examples of natural products described in the literature, including the synoxazolidinones.The synthesis of synoxazolidinones A and B achieved by Pierceis presented, before to introduce the target molecule synoxazolidinone C. The isolation, structure, biological activity as well as a proposed biosynthesis of this compound will be shown. The Chapter ends with different methods used to build the fused bicyclic ring skeleton and an initial strategy towards the total synthesis of synoxazolidinone C. Chapter 2 focuses on the synthesis of the conjugated bicyclic ring skeleton with the substituents on the aromatic ring as present in the natural product. The Chapter begins with the study of a double ring closure mechanism towards the fused bicyclic ring skeleton with an aromatic substituent and its oxidation to install the conjugated double bond in between. The synthesis was modified to build the fused bicyclic ring and the double bond in one step. A suitable aromatic building block was then prepared to access the desired analogue of the natural product without substituents on the pyrrolidine ring. Chapter 3 explains the work towards the synthesis of deschloro-synoxazolidinone C, desguanidino-synoxazolidinone C, and the natural product synoxazolidinone C itself. With the revised strategy detailed in Chapter 2, the suitable amines were prepared to access the conjugated bicyclic ring with additional substituents on the pyrrolidine ring. Those substituents are used in an effort to install the chlorine and the guanidine. A brand new condensation double ring closure methodology was also developed as a rapid access to a late stage material towards deschloro-synoxazolidinone C. Chapter 4 describes a structure-activity relationship; it presents the biological evaluation of 18 synthetic analogues of the natural product. Several assays were performed such as the viability, anti-inflammatory, minimuminhibition concentration (MIC), inhibition of biofilm and antioxidant.